2002
DOI: 10.1108/13620430210421614
|View full text |Cite
|
Sign up to set email alerts
|

Leaving and experiencing: why academics expatriate and how they experience expatriation

Abstract: Globalisation has led to increasing international mobility amongst business and education professionals. Whilst expatriate management literature focuses on expatriate assignment of corporate executives, expatriate academics remain an under researched group. Higher education literature has focused on internationalisation of education systems, notably the growth in international strategic alliances between universities, and mobility amongst students. Therefore compared with what is known about the student body, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 26 publications
7
184
2
Order By: Relevance
“…Different metaphors have been used to explain the motivating grounds for selfinitiated expatriation (Richardson & McKenna 2002, 2003Selmer & Lauring 2010;Doherty, Dickmann, and Mills 2011). The primary reasons for this type of expatriation are considered to be: 1) explorer instinct, 2) fleeing the familiar, 3) quest for better wages and 4) career development considerations.…”
Section: Motivations For Expatriationmentioning
confidence: 99%
“…Different metaphors have been used to explain the motivating grounds for selfinitiated expatriation (Richardson & McKenna 2002, 2003Selmer & Lauring 2010;Doherty, Dickmann, and Mills 2011). The primary reasons for this type of expatriation are considered to be: 1) explorer instinct, 2) fleeing the familiar, 3) quest for better wages and 4) career development considerations.…”
Section: Motivations For Expatriationmentioning
confidence: 99%
“…Within the British context, the need for adventure or travel has been found to be a factor that influences movement of skills (Richardson & Mallon, 2005;Richardson & McKenna, 2002). In another study, the need for financial gain and the quest for career development opportunities have been found to influence the movement of younger academics to leave their home countries (Selmer & Lauring, 2010).…”
Section: Factors Influencing Self-initiated Expatriate's Movementmentioning
confidence: 99%
“…In addition, through good resources and facilities, participants were able to advance and develop their careers (Andresen et al, 2012). Participants of this research can be viewed as refugees who are architects and mercenaries (Fitzgerald & Howe-Walsh, 2008;Richardson & McKenna, 2002). This research revealed that SiEs are not solely driven by the desirability of the job, but rather the poor economic and political conditions in their home countries.…”
Section: Relating Main Findings To Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Both approaches have their strengths and weaknesses as researchers attempt to control a variable (host or home country) in order to emphasize either brain drain or brain gain. For example, one study examined 30 British academics who work around the world (Richardson and McKenna 2002) while another examined foreign academics who work in South Korea (Kim 2016). This literature review first covers scholarly works that deal with internationally mobile academics followed by studies on mobile professionals in general.…”
Section: Literature Reviewmentioning
confidence: 99%